Supporting Preschool Teachers and Candidates in Inclusive Preschool Setting – Presentation of Naturalistic Teaching Project - Böddi, Zsófia; F. Lassú, Zsuzsa; Kerekes, Valéria; Svraka, Bernadett (Gyermeknevelés Tudományos Folyóirat, 2025)
Although mainstream teachers have wide knowledge about children with special educational needs (SEN), improvement of practical skills regarding education and development of these children is always needed. Improving teaching skills related inclusion and best practices are very important, as well as exchanging inclusion-related information and experience with other countries. Naturalistic teaching is defined as a process that helps children to gain developmental goals through interactions with the teacher embedded in natural environment and situations. It is a process, which provides developmental opportunities for all young children with SEN at-risk groups and with typical development to acquire skills or reinforce them. This paper presents the characteristics of Naturalistic Teaching as well as the key elements of it. The main questions and strategies are also described such as strategies that can be used with both children with and without SEN. Naturalistic Teaching Project is also presented as a good example of international information changing in the field of preschool inclusion.